Natural Antidepressant Candidate from Cassia alata L. Ethanolic Extract: Behavioral (TST-FST) Evidence in Mice - Putri, Kristina Srirahayu Damaiyanti; Nabella, Juwita Rosalia Sintia; Su’aida, Nily; Erlianti, Karina (Sciences of Pharmacy, 2026)
Cassia alata L. is a medicinal plant containing various secondary metabolites with reported neuroactive properties. This study aimed to evaluate the antidepressant-like behavioral effects of the ethanolic extract of Cassia alata Leaves in mice using acute behavioral despair tests. Male mice (n = 5 per group) were orally administered ethanolic extract of Cassia alata leaves at doses of 100, 200, and 400 mg/kg body weight. A sub-acute stress exposure protocol using the Tail Suspension Test was applied, and antidepressant-like activity was subsequently evaluated using the Forced Swimming Test, with immobility time at T2 as the primary outcome measure. Amitriptyline served as the standard drug. Data were analyzed using one-way ANOVA followed by Tukey’s HSD post hoc test (p0.05). Chemical profiling was performed using LC–MS/MS. One-way ANOVA revealed a significant difference in immobility time among groups (F (4,20) = 21.465, p0.001). Post hoc analysis showed that all extract-treated groups exhibited significantly lower immobility times compared to the negative control (p0.05). The highest dose (400 mg/kgBW) was not significantly different from amitriptyline (p0.05), while lower doses showed intermediate effects. LC–MS/MS analysis tentatively identified 17 compounds, including flavonoid derivatives, luteolin, and anthraquinones. Under the present experimental conditions, the ethanolic extract of Cassia alata leaves exhibited antidepressant-like behavioral activity in acute animal models. These findings are limited to short-term behavioral observations and do not establish clinical efficacy, safety, or underlying mechanisms. Further studies are required to clarify the pharmacological relevance and translational potential of this extract.